Manajemen Islam Perusahaan : Model Dan Praktis - Haanurat, Ifayani; Suarni, Agusdiwana; Haliding, Safri (Jurnal Ekonomi Balance, 2011)
Islamic syariah is a comprehensive guide of life,Â  coveringÂ  of all aspect of life. Syariah is not only set the ruleÂ  of the transcendental relationship between muslim and AllahÂ  SWT but provided for every aspect, one of the rules is organizing institutions. Therefore, Islam has also Islamic management conceptÂ  Islamic management reguires the leaders of organization are able to do a holistic approach with the God concept by giving their outhority to the God with humility, responsibility and independence to fulfill their duties and practice Islamic management with flexibleÂ  modelÂ  for maximum result.Islamic management of organization should be viewed as a means to facilitate the implementation of Islamic in the activities of the organization. Implementation of Islamic values as intangibles in our thinking and activities in all aspects of organization. Thus, The values of Islamic is actually the organizationâs core values. TheÂ  Islamic values will become the strategic of organization.